The SAGE handbook of the philosophy of social sciences - Jarvie, I. C. (Ian Charles), 1937-; Zamora Bonilla, Jesus P. (London : SAGE Publications, 2011)
This handbook provides a comprehensive view of the fundamental philosophical and methodological problems characteristic of the social sciences, as well as of the main approaches and school of thought within the discipline. It is a reference for researchers and teachers to employ in their investigations and lectures.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 17, 2014).
Keywords: elektronické knihy; electronic books; Social sciences -- Philosophy